Screening of indole-3-acetic acid PGPB from three agricultural systems at Nakhon Pathom, Thailand - METHANEE HOMTHONG; WANPHEN KAEWPUK; SUKANYA YAMSUAN; ANUNYA THONGSIMA; KANLAYA MOKKAPAN; VACHIRAPORN PIKULTHONG (Society for Indonesian Biodiversity, 2022)
Abstract. Homthong M, Kaewpuk W, Yamsuan S, Thongsima A, Mokkapan K, Pikulthong V. 2022. Screening of indole-3-acetic acid PGPB from three agricultural systems at Nakhon Pathom, Thailand. Biodiversitas 23: 5935-5941. Plant growth-promoting bacteria (PGPB) are associated with plant roots and enhance growth via a variety of mechanisms, including fixation of atmospheric nitrogen, solubilization of phosphorus, phytohormone synthesis, and plant phenolic compound stimulation. Sixty-five isolated bacteria from the three agricultural systems in Nakhon Pathom were screened for IAA production. The results showed that seven isolates—C01-28, C02-48, C02-51, G01-34, G03-25, G03-38, and O02-46—produced IAA under L-tryptophan as a precursor at values of 9.08 ± 0.51, 68.64 ± 29.07, 40.67 ± 18.04, 10.65 ± 1.07, 63.30 ± 1.15, 37.73 ± 1.80, and 121.28 ± 15.20 mg mL-1, respectively. Capability on plant growth-promoting traits revealed that none of the isolates stimulated ten-morning glory (Ipomoea aquatica Forsk.) seedling growth, which was not significantly different from the control. Isolates O02-46 enhanced salicylic acid (SA) in ten-morning glory seedlings the most, showing 7.18 ± 1.78 µg g-1 of fresh weight, while isolates G01-34 enhanced phenolic compound (PC) production the most showing 218.18 ± 29.55 mg GAE g-1 extract, respectively. The 16S rRNA analysis revealed that isolates O02-46, C02-48, G03-25, and C02-51 were identified as similar to Paenibacillus alvei at 99.20% (Accession number AY826588.1), Bacillus megaterium at 79.91% (Accession number MH031358.1), Bacillus sp. at 98.57% (Accession number JF322976.1), and Lysinibacillus fusiformis at 99.61% (Accession number HE610782.1).